(untitled) (Texas Journal of Philology, Culture and History, 2021)
Problem-based learning - learning in which the teacher systematically creating problem situations and organizing the activities of students to solve problems, provides an optimal combination of their independent, search activities with the assimilation of ready-made conclusions of science. The organization of problem-based learning is based on the principle of personality and activity, i.e. the discovery by students under the guidance of a teacher of the conclusions of science, methods of action, the invention of new objects or methods of applying knowledge to practice